The effect of involuntary maternal job loss on children's behaviour and non-cognitive skills - Frauke Peter (Labour Economics, 2016)
This paper uses propensity score methods to analyse the effect of involuntary maternal job loss on children's non-cognitive skills. My analyses are based on a rich and nationwide random sample, the German Socio-Economic Panel Study (SOEP) that includes information about maternal job loss and child behaviour and non-cognitive skills, in addition to a rich conditioning set. The results show that maternal job loss increases preschool children's socio-behavioural problems and decreases adolescents' belief in self-determination.
Keywords: J13; J63; J65; 330; Child development; Maternal job loss; Non-cognitive skills; Propensity score methods